Opportunities of Traditional Law Communities to Resolve Criminal Cases in Indonesia (Response to the Long Crisis of Legality Issues in the Principles of Criminal Law) - Irma Fatmawati (Budapest International Research and Critics University, 2021)
The formalization of law in Indonesia is the climax of the reification process. This reification occurs because it is controlled and nominated by the ruling class in the interpretation of the law. Legal arguments are made in a repressive condition because they must be supported by a legal arrangement that seems to explain social conditions comprehensively. On the other hand, each law is a system; that is, the rules are unanimous based on the mind's unity. Legal entities in Indonesia (as incarnations in customary law) are a system that is based on the basics of the Indonesian nation's reason, which is not the same as the mind that controls the western legal system. To be aware of the legal entity system in Indonesia, one must explore the essential nature of the reason that exists in Indonesian society. However, the principle of concordance seems to have been ingrained among legal experts in this Republic, so that the legal system is not adopted unequally, the Western legal system dominates the national legal system, so that the religious and customary law systems have less room to be enforced by the state. That is why The familiar law system and the Islamic legal system in Indonesia are not developed and are not well absorbed in the national legal system; this indication can be seen from the percentage of statutory legal products produced by the state which adopt more Western legal strategies such as the Civil Code, the Criminal Code. Commercial Code, Human Rights (HAM) law. In the context of the development of Indonesian law, demands to revise and even replace various laws and regulations originating from the Dutch colonial such as the Criminal Code, the Civil Code, which are no longer by the identity of the Indonesian nation, the renewal of these provisions is a historical necessity and a non-negotiable constitutional imperative. This research is library research.. The method used in this research is the method of philosophical hermeneutics, with the following elements: interpretation, description, and comparison. The study results indicate that, in reality, today, the practice of applying the small claim court mechanism in positive Indonesian criminal law has been widely used in various disputes that occur in society, especially against crimes that are light and not difficult to prove.